The effect of hyperbaric oxygenation on cardiodynamics and oxidative stress in rats with sepsis - Jevtić, Aleksandar; Živković, Vladimir; Milinković, Milica; Mijailović, Željko; Draginić, Nevena; Andjić, Marijana; Milojević Šamanović, Andjela; Bolevich, Sergey; Jakovljević, Vladimir (Vojnosanitetski pregled, 2021)
Background/Aim. Dysfunctions at the cellular, tissue, and organ level, which can result in death, are caused by metabolic changes and affection on the regulation of gene transcription and micro- and macrocirculation. The aim of the present study was to assess the impact of hyperbaric oxygenation (HBO) on isolated heart as well as on the oxidative status of rats with sepsis. Methods. The investigation included male Wistar albino rats classified into three groups: the first group was a control group (CTRL); the second group included animals exposed only to the induction of sepsis without HBO treatment (the Sepsis group), while the third group included animals treated with HBO after the induction of sepsis (the Sepsis + HBO group). For the induction of sepsis, fecal peritonitis model was used (3 mL/kg of fecal suspension administered intraperitoneally). After the induction of sepsis, the rats were exposed twice a day (on 12 hours) to HBO treatment at 2.8 atmospheres absolute (ATA) for 90 minutes over a period of 3 days. 72 h after the confirmation of sepsis, the animals were sacrificed and the hearts were retrogradely perfused on the Langendorff apparatus at a gradually increased coronary perfusion pressure (CPP = 40–120 cm H2O). The following parameters of heart function were continuously recorded: maximum and minimum rate of left ventricular pressure development (dp/dt max, dp/dt min); systolic and diastolic left ventricular pressure (SLVP and DLVP); heart rate (HR). Coronary flow (CF) was measured flowmetrically. Following oxidative stress markers were measured: nitrites (NO2−), superoxide anion radical (O2−), hydrogen peroxide (H2O2), index of lipid peroxidation (TBARS), activity of superoxide dismutase (SOD) and catalase (CAT) and the level of reduced glutathione (GSH). Results. There were no significant differences in dp/dt max, dp/dt min, SLVP and HR between the groups. CF was statistically significantly higher (p < 0.01) in the sepsis group. The values of all cardiac oxidative markers were lower in the sepsis + HBO group (p < 0.05), while systemic pro-oxidative and antioxidative parameters were unchanged. Conclusion. Our results showed that HBO treatment was not associated with improved cardiac function and coronary perfusion, while expressed promising beneficial effects on cardiac oxidative stress.
Keywords: hyperbaric oxygenation; oxidative stress; sepsis; heart; rats